PENGARUH PENGGUNAAN METODE EVERY ONE IS A TEACHER HERE TERHADAP MOTIVASI BELAJAR SISWA KELAS V PADA PEMBELAJARAN IPS SDN 4 TUGUMULYO - Bagus Okta Fitra; Ilham Arvan Junaidi; Ida Suryani (Universitas Negeri Medan, 2022)
Abstract : The effect of using every one is a teacher here method on learning motivation of v grade students in ips learning in sdn 4 tugumulyo. This study aims to determine the effect of using the every one is a teacher here method on the learning motivation of fifth grade students in social studies learning at SDN 4 Tugumulyo. The research method in this study used an experimental method with a one group pretest-posttest type design, the population in this study amounted to 34 students from all fifth grade students at SDN 4 Tugumulyo. The data collection technique in this study used a questionnaire. Content validity was obtained from expert judgment and construct validity was calculated using product moment correlation by Pearson and reliability using Cronbach's Alpha. The data analysis technique used in this study was the normality test with Shapiro Wilk, the homogeneity test with the Levene test and hypothesis testing with the Paired Sample T-test. The results showed that there was an effect of using the every one is a teacher here method on the learning motivation of fifth grade students in social studies learning at SDN 4 Tugumulyo. It is shown from the results of the Paired Sample T-test of the pretest and posttest of learning motivation, it was found that the significance value of Sig (2-tailed) was 0.000 < 0.005, so was rejected and was accepted. Keyword : The Every One Is a Teacher Here Method, Motivation to learn Abstrak : Pengaruh penggunaan metode every one is a teacher here terhadap motivasi belajar siswa kelas v pada pembelajaran ips sdn 4 tugumulyo. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan metode every one is a teacher here terhadap motivasi belajar siswa kelas V pada pembelajaran IPS SDN 4 Tugumulyo. Metode penelitian pada penelitian ini menggunakan metode eksperimen dengan desain tipe one group pretest-posttest, populasi pada penelitian ini yaitu berjumlah 34 siswa dari seluruh siswa kelas V SDN 4 Tugumulyo. Teknik pengumpulan data pada penelitian ini menggunakan angket. Validitas isi diperoleh dari judgment ahli dan validitas konstruk dihitung menggunakan korelasi product moment oleh pearson dan reliabilitas menggunakan Alfa Cronbach. Pada penelitian ini, teknik analisis data yang digunakan yakni uji normalitas dengan Shapiro Wilk, uji homogenitas dengan uji Levene dan uji hipotesis dengan Paired Sample T-test. Hasil penelitian menunjukkan bahwa adanya pengaruh penggunaan metode every one is a teacher here terhadap motivasi belajar siswa kelas V pada pembelajaran IPS SDN 4 Tugumulyo. Hal itu ditunjukkan dari hasil uji Paired Sample T-test data pretest dan posttest motivasi belajar didapatkan nilai signifikansi Sig (2-tailed) 0,000 < 0,005 maka ditolak dan diterima. Kata Kunci : Metode Every One Is a Teacher Here, Motivasi Belajar